Efektivitas Model Pembelajaran Flipped Classroom (FC) Terhadap Kemampuan Berpikir Kritis Matematis Siswa pada Materi Peluang - Indah Sari Dewi; Nurul Husna; Rosmayadi Rosmayadi (LP. Ma'arif Janggan Magetan, 2024)
The purpose of the study is to determine the achievement of student learning completeness on opportunity material after applying the Flipped Classroom (FC) learning model, knowing whether the mathematical critical thinking skills of students who get learning with the Flipped Classroom (FC) learning model are better than students who get learning with the direct learning model and to find out student learning activities during the application of the Flipped Classroom (FC) learning model. This study used a Quasi-Experimental design with the form of The Nonequivalent Posttest-Only Control Design. The population in this study was all grade VIII students of SMP Negeri 6 Singkawang totaling 115 students and the sample in this study consisted of 2 classes selected from 5 classes. Sampling using purposive sampling technique and selected class VIII E as experimental class and class VIII B as control class. The consideration of choosing the two classes is because there are still many students who have difficulty in learning and the average completeness of students has not reached KKM. Data collection is carried out by providing posttest questions on opportunity material and observation of student learning activities. Hypothesis testing using one sample t-test, two sample t-test. The results showed that: 1) Students achieved individual and classical completeness in classes applied to the Flipped Classroom (FC) learning model; 2) The mathematical critical thinking ability of students applied the Flipped Classroom (FC) model is better than students who applied the direct learning model; 3) Student activities are classified as active during the implementation of the Flipped Classroom (FC) learning model.